IMPLEMENTING AND MEASURING IMPACT OF A FIVE-YEAR TRANSLATIONAL GERIATRIC ONCOLOGY RESEARCH PROGRAM. (20th December 2022) - Blackberry, Irene; Steer, Christopher; Rasekaba, Tshepo; Rich, Stacey; Webb, Nicole; Young, Kim
Abstract: The Geriatric Oncology Regional Victorian Trials Alliance, Linkages, Special populations, Equity program (GO ReViTALISE) is part of a five-year state-wide grant to increase access to cancer clinical trials in regional Victoria, Australia. The initiative covers engagement with key stakeholders and trial sites, co-design of research programs with consumers, implementation of multiple interventional and non-interventional research, and capacity building. Employing a framework prospectively is critical to guide and scaffold implementation of complex interventions and capture the process of how several activities interact. Likewise, there is a need to show research impact beyond successful implementation and clinical outcomes. Using the GO ReViTALISE as a case study, we will demonstrate how an implementation framework and the Framework to Assess the Impact from Translational health research can deliver a cohesive, impactful and measurable program of research to increase older adults' participation in cancer clinical trials, trials availability and build capacity in regional cancer sites.